Alcohol Use Disorder and Initiation of Oral Anticoagulant Therapy in Patients with Atrial Fibrillation: A Nationwide Cohort Study - Vanhanen, Miika (My University, 2025)
Objective:Patients with alcohol use disorders (AUD) often receive inferior care for somatic comorbidities. Our objective was to explore whether AUDs influence oral anticoagulant (OAC) initiation for stroke prevention among atrial fibrillation (AF) patients, using a nationwide dataset to assess treatment disparities.Methods:The Finnish AntiCoagulation in Atrial Fibrillation registry includes data on all 229,565 patients diagnosed with incident AF in Finland during 2007-2018, identified from national registries covering all levels of care. The main outcome was OAC initiation compared between patients with and without AUD.Results:The patients’ mean age was 72.7 years, 50% were female, 85.0% were eligible for OAC therapy (CHA2DS2-VA score ≥1), and 4.7% had AUD. OAC therapy was initiated in a smaller proportion of patients with AUD compared to those without (52.5% vs. 71.4%, p<0.001). This disparity remained significant even after adjusting for comorbidities, socioeconomic status, and laboratory values influencing OAC initiation (adjusted hazard ratio [HR] 0.68; 95% confidence interval [0.66-0.71]). The absolute difference in OAC initiation between groups stayed consistent at approximately 20% throughout the study period. Interaction analyses indicated that the association between AUD and lower OAC initiation was stronger in patients with lower income, lower educational attainment, and lower thrombocyte levels, but there was no significant interaction with sex, bleeding history, or hemoglobin levels.Conclusions:AUDs are associated with a significantly lower rate of OAC initiation even after accounting for comorbidities that influence OAC initiation.
Keywords: alcohol, use, disorder, AUD, alcohol, atrial, fibrillation, af